2011
DOI: 10.1074/jbc.m110.143198
|View full text |Cite
|
Sign up to set email alerts
|

Role of Swi6/HP1 Self-association-mediated Recruitment of Clr4/Suv39 in Establishment and Maintenance of Heterochromatin in Fission Yeast

Abstract: Swi6/HP1, an evolutionarily conserved protein, is critical for heterochromatin assembly in fission yeast and higher eukaryotes. In fission yeast, histone deacetylation by histone deacetylases is thought to be followed by H3-Lys-9 methylation by the histone methyltransferase Clr4/Suv39H1. H3-Lys-9-Me2 interacts with the chromodomain of Swi6/HP1. Swi6/HP1 is thought to act downstream of Clr4/Suv39, and further self-association of Swi6/HP1 is assumed to stabilize the heterochromatin structure. Here, we show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…Furthermore, it has been proposed that the physical interaction of Clr4 with Swi6 is important for the establishment/spreading of H3K9 methylation (30). A similar functional concept for the Suv39h-HP1 complex on the H3K9me-mediated heterochromatin establishment/spreading has been proposed for other species, including mammals (11,12).…”
Section: Hp1 Binding To Suv39h1 Was Dispensable For the Establishmentmentioning
confidence: 87%
“…Furthermore, it has been proposed that the physical interaction of Clr4 with Swi6 is important for the establishment/spreading of H3K9 methylation (30). A similar functional concept for the Suv39h-HP1 complex on the H3K9me-mediated heterochromatin establishment/spreading has been proposed for other species, including mammals (11,12).…”
Section: Hp1 Binding To Suv39h1 Was Dispensable For the Establishmentmentioning
confidence: 87%
“…HP1 proteins have been proposed to act as platform molecules that recruit diverse activities to heterochromatic regions 1,17,1922 . The best-characterized HP1 domain that is known to recruit non-nucleosomal ligands is the CSD.…”
Section: Resultsmentioning
confidence: 99%
“…CSDs are dimerization domains of HP1 proteins that serve as interaction interfaces that stabilize heterochromatic structures (60). Mutations that interfere with HP1 dimerization disrupt the protein's localization to heterochromatin (6,61). Similarly, we recently showed that mutation of the Pdd1 CSD severely reduces production of viable progeny and inhibits formation of DNA elimination foci; however, some IES excision still occurred, which suggests that other proteins, possibly including Lia4, contribute to the overall stability of DNA elimination complexes (37).…”
Section: Discussionmentioning
confidence: 99%